QUANTITATIVE GEOMORPHOLOGY EXPRESSION OF GEOLOGICAL STRUCTURES USING SATELLITE IMAGERY AND GEOSPATIAL ANALYSIS: AN EXAMPLE IN THE SOUTHERN PART OF MERAPI MOUNT, YOGYAKARTA, INDONESIA - Riswandi, Herry; Sukiyah, Emi; Tania, Dina (Journal of Geological Sciences and Applied Geology, 2021)
Research using morphotectonics parameters from a 30-m digital elevation model to evaluate satellite imagery data. It process by contour, slope, aspect, and hillshade analysis of geographic information system tools. For geological lineaments, drainage patterns and their relation with geological structures. Data analyzed in digital format reveals the lineament identifies 116 segments in north-south and east-west polar direction, with length from 0.2 to 4.6 km. Quantitative geomorphology is based on the slope and valley dimension in four watersheds to recognize recent tectonic activity located on the southern slopes. Digital quantitative geomorphic analyzed volcanic slope area to generate data along with the tectonic evolution in annual eruption. Furthermore, the results become references for recent tectonic activity on the volcanic slopes, with several exceptional values of the four watersheds. That indices of bifurcation ratio, drainage density (3.44-4.76), sinuosity of mountain front (3-4), valley floor width to valley height ratio (0.021-0.32), asymmetry factor (16.7-2), streams length gradient index (5.9-12.2),  hypsometric (h/H 0.4-0.6 and a/A 0.4-0.5), transverse topography symmetry (0.47-0.87), elongation of basin ratio (0.003). The analyzed data results that structures are shifting. The geomorphological index can support tectonic activity assessment through the deformation of land from various volcanic deposits, uplift rate, and asymmetric river maturity.